Distribution and community structure of at-risk and Data Deficient elasmobranchs in Zavora Bay, Mozambique. Issue 4 (2nd October 2021) - O'Connor, B; Cullain, N
Abstract : Persistent threats from fishing pressure and increasing habitat degradation, as well as slow recovery rates resulting from K -selected life histories, are putting increasing numbers of elasmobranch species (sharks, rays and skates) at risk of extinction worldwide. Global declines in elasmobranch populations merit evidence-based conservation measures, but establishment of such measures has been hindered by a paucity of population-level data. Mozambique supports a high number of threatened (Vulnerable, Endangered or Critically Endangered) and Data Deficient elasmobranch species; however, most of these populations are poorly understood. We collected baseline data on the presence, species richness, diversity, and habitat use of elasmobranchs within Zavora Bay, Mozambique, using baited remote underwater video and underwater visual census surveys, at six sites, from January 2017 to March 2020. Our results show that Zavora Bay is used year-round by 20 elasmobranch species, all of which are listed on the IUCN Red List of Threatened Species as either Data Deficient, threatened, or Near Threatened with declining population trends. Many of these species are heavily targeted by fisheries or caught as bycatch throughout their range, and some do not encounter protected areas anywhere within their natural range, highlighting the urgency to establish adequate conservation strategies to prevent further population declines.